Pengaruh Hubungan, Emphaty, Nilai Dan Kepercayaan Terhadap Kepuasan Nasabah Pada Pt. Bank Sulselbar Cabang Utama Makassar: indonesia - Sujatmiko, Sujatmiko; Pratiwi Ar, Dhita; Hamdat, Amiruddin; Panus, Panus; Amelia, Reski (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2023)
Customer satisfaction is the level of a person's emotional state that is the result of a comparison between the performance appraisal/final product in relation to customer expectations and they can convey what and how their needs are. This study aims to examine and analyze the effect partially or simultaneously between relationships, emphaty, values and trust on customer satisfaction. Data collection using primary data obtained from customers at PT. Bank Sulselbar Makassar Main Branch where sampling uses the slovin formula where after doing calculations using the slovin formula sets a sample of 100 respondents. The results of the questionnaire have been tested for validity and reliability, as well as classical assumptions in the form of Normality, Multicolonerity Assumption, and Heteroscedasticity. The data analysis method uses multiple linear regression analysis assisted by the SPSS 23 program (Statistical Program For Social Science). The results showed that both partially and simultaneously relationships, emphaty, values and beliefs had a positive and significant effect on customer satisfaction so that all hypotheses proposed were accepted